Read till it shatters Nationalism and identity in modern Thai literature - Chaloemtiarana, Thak (ANU Press, 2018)
This book introduces readers to modern Thai literature through the themes of modernity, nationalism, identity and gender. In the cultural, political and social transformations that occurred in Thailand during the first half of the twentieth century, Thai literature was one of the vehicles that moved the changes. Taking seriously 'read till it shatters', a Thai phrase that instructs readers to take apart the text, to break it down, to deconstruct it, Thak Chaloemtiarana challenges the Thai literary canon from the margins and suggests ways of expanding and enriching it. Thai literature is scarce in translation and requires the skills of a scholar fluent in Thai to comprehend it. Thak is a political scientist turned literary scholar who is bilingual in Thai and English and an avid reader of Thai fiction by authors up and down the social scale. Here he offers lively insights into his favourite literary genres with fresh readings of early Thai novels, Sino-Thai biographies and memoirs of the rich and famous. 'Thak Chaloemtiarana is an inquisitive man. Late in his career he switched from politics to literature. In these chapters, he draws on a lifetime of reading about writers and writing in Thailand over the past century. He nods towards the usual big names-King Vajiravudh, Luang Wichit, Kulap Saipradit, Kukrit Pramoj-but spends more time on those found in the lesser visited stacks of the libraries, the secondhand bookstalls, and the shelf by the supermarket checkout. His themes are familiar-Thailand and the West, Thai nationalism, the Thai-Chinese, and women under patriarchy-but the angles of vision are original. With a cast ranging from motor-racing princes through sexy Egyptian mummies and a feminist serial murderer to starlets touting breast-enhancement techniques, this book educates, enlightens, and entertains.'